USING CHICKEN GROWTH SIMULATOR IN TEACHING POULTRY PRODUCTION IN SECONDARY SCHOOL: IMPLICATION FOR EFFECTIVE POULTRY MANAGEMENT - Godwin Udo, Ukpong (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2023)
Farm simulation software can be efficient for poultry management and agricultural-related courses. However, limited research has demonstrated their efficacy in secondary school education in Nigeria. The present study examined the effect of chicken growth simulation on students' interest in poultry production. Two hundred and nine secondary school students conveniently pooled from different secondary schools in Omoku River State participated in the study. The respondents were taught the poultry management process using the chicken simulation software. Their interest in poultry production was examined using a questionnaire. The result established a statistically significant effect of chicken growth simulation software on the respondent's intention to engage in poultry production at F (1,207), 4.60 P< .05 with adjusted R2 indicating that the chicken growth simulation software contributed about 29.8% of the variance in student's intention to engage in poultry farming. The result has implications for effective poultry management.